2016
DOI: 10.1556/030.63.2016.003
|View full text |Cite
|
Sign up to set email alerts
|

Ebola virus disease: Awareness among dental students in Hungary

Abstract: Introduction: The Ebola epidemic has claimed thousands of lives in Africa, and there has been a mounting pressure on the healthcare systems around the globe to prepare for the showing up of patients infected with this virus. Junior clinicians are at the forefront of medical teams, often coming into contact with patients first, during clerking and admissions. This study assesses the level of knowledge of Ebola virus disease (EVD) among dental students at Semmelweis University, Budapest, Hungary. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…According to the findings of our study, overall majority had an appropriate level of knowledge about the Ebola virus consistent to other analogous studies. 10,11 However, a significant difference is observed between the disciplines of health care professionals who were included into our study. Approximately, 44% of the health care professionals other than doctors were found to have better knowledge about Ebola virus as compared with doctors parallel to results of a similar study.…”
Section: Discussionmentioning
confidence: 89%
“…According to the findings of our study, overall majority had an appropriate level of knowledge about the Ebola virus consistent to other analogous studies. 10,11 However, a significant difference is observed between the disciplines of health care professionals who were included into our study. Approximately, 44% of the health care professionals other than doctors were found to have better knowledge about Ebola virus as compared with doctors parallel to results of a similar study.…”
Section: Discussionmentioning
confidence: 89%
“…In Hungary among 267 dental students a survey was conducted about the ebola virus 16 . Due to the improper diet and improper food habits there are many chances to cause ebola virus.so they need to intake proper food to prevent them from the disease 17 .…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Salman et al 15 among Pakistani university students showed that most students also have poor knowledge of EVD (91.8%). Károlyházy et al 16 conducted a study among dental students in Hungary and reported poor knowledge of EVD. Moreover, Fazekas et al 17 conducted a study among junior doctors in England and showed that surveyed doctors have poor awareness regarding EVD.…”
Section: Discussionmentioning
confidence: 99%